The Doctrine of Islamic Values Through the Curriculum: a Case Study at the Madrasah Hurrasul Aqidah Tarakan City - Zainal Abidin Muhja; Liza Shahnaz; Siti Rohmah (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
The purpose of this study is to describe how and what are the doctrines of Islamic values ​​through the curriculum in educational institutions. The existence of Islamic education is to preserve the proper value system of piety. Because it is human nature that specific value systems also demand a developed education system, the strategies adopted, the techniques used, the subject matter as content, and the policies from the lowest level of an institution to the main level with a comprehensive and integrated curriculum system, all of which should not be contrary to the Islamic value system as a fitrah. This research uses qualitative research by taking data at Madrasah Hurrasul Aqidah Tarakan City as the object of research, data collection techniques used are observation, interviews and documentation; analytical tools used are Miles and Huberman qualitative analysis models, checking the validity of data using triangulation. This study resulted in five doctrinal values ​​through the curriculum, namely: strengthening the Islamic aqidah uluhiyah-rububiyah-asma wa shifat in students' daily lives, emphasizing habituation of sunnah worship integrated with fiqh subjects, habituation of civilized characters with examples and directions, tahfidh al-qur'an it is mandatory for all students to have the vision of creating a Qur'anic generation, and tadabbur alam (knowing God's creation) as natural learning media. This study is oriented by integrating Islamic values ​​in the core and extra curriculum as the doctrine of giving birth to an Islamic generation (qur'ani); this emphasizes the critical role of vision and mission in a robust educational institution that characterizes the output of its graduates because the cases generally follow the general policy of the government only.